Knowledge, Spirit, Law, Book 1: Radical Scholarship - Keeney, Gavin (Book collections on Project MUSE., 2020)
As the author-pay model spreads across academic publishing, what are the possible consequences? Will the current rage for open-source scholarship actually accomplish anything other than shifting the furniture around on the Titanic? Will not Open Source in combination with Digital Humanitiesfurther destroy the very idea of "slow" and "thoughtful" work in humanistic studies?...It would seem that the author-pay model (formerly attributed to predatory publishers) is just another way of extracting tribute for the "privilege" of being published--enforceable only because academia has ratcheted up the stakes by enforcing research metrics and citations, in the public universities a practice that is primarily enforced by external "industrial" connections. Almost all public and private universities are heading toward measuring output with metrics--many academics now tailoring their CVs to show why they are "important," mirroring the social-media campaigns of celebrities and politicians, and many universities now citing their own "corporate" rankings when promoting their product (the University, the Institute, the Department, the Professor). Where this is all going is toward increased precarity for anyone who does not play the game. Individual, solitary scholars will have few options. Gavin Keeney, "Symptom 'A': The End," Knowledge, Spirit, LawKnowledge, Spirit, Law -- as project -- is a de facto phenomenology of scholarship in the age of Cognitive Capitalism. The six essays (plus Appendices) presented here cover topics and circle themes related to the problems and crises specific to neo-liberal academia, while proposing creative paths around the various obstructions. The obstructions include metrics-obsessed academia, circular and incestuous peer review, digitalization of research as stalking horse for text- and data-mining, and violation by global corporate fiat of Intellectual Property Rights and the Moral Rights of Authors. These issues, while addressed obliquely in the main text, definitively inform the various implied proscriptive aspects of the essays and, via the Introduction and Appendices, underscore the necessity of developing new-old means to no obvious end in the production of knowledge -- that is to say, a return to forms of non-instrumentalized intellectual inquiry. To be developed in two concurrent volumes, Knowledge, Spirit, Law will serve as a "moving and/or shifting anthology" of new forms of expression in humanistic studies.